Integrasi Agama dan Sains: Penafsiran Peristiwa Hari Kiamat pada Tafsir Salman ITB Dan Tafsir Ilmi Kemenag RI-LIPI - Ummul Hikmah; Zulheldi Zulheldi; Widia Fithri (Institut Agama Islam Sumatera Barat, 2023)
The Day of Judgment is a very frightening event for all humans. The events that occurred on that day are very much explained in the Qur'an, but this study will examine the events of the Day of Judgment according to the interpretation of Salman ITB and Tafsir Ilmi Kemenag RI-LIPI. The two books of interpretation have a scientific approach, but in terms of their authors, the background is different, the book of interpretation of Salman ITB is the work of ITB alumni in the field of science, while the book of Tafsir Ilmi Kemenag RI-LIPI has a background of scholars. This study will discuss the interpretation of the events of the Day of Judgment according to the interpretations of Salman ITB and Tafsir Ilmi Kemenag RI-LIPI using an integration approach. The results of this study can be concluded, that the doomsday events that occur on earth (Earth, Mountains and Seas) in the book of Tafsir Salman ITB explain more related to science than the interpretation in the book of Tafsir Ilmi Kemenag RI-LIPI. The integration pattern used by Tafsir Salman ITB tends to be a dialogue pattern. While the interpretation of doomsday events that occur in the sky (sky, sun, moon and stars) the two interpretations look balanced, but in their integration, the interpretation of the book of Tafsir Ilmi Kemenag RI-LIPI tends to see the pattern of integration and the interpretation of Salman ITB looks more using the pattern dialog.